Kemampuan Literasi Matematika Pada Pemecahan Masalah HOTS (High Order Thinking Skills) Peserta Didik Kelas VIII SMP Negeri 4 Brang Rea Tahun Pelajaran 2020/2021 - Fidya Rizta Amalia; Arjudin Arjudin; Syahrul Azmi; Hapipi Hapipi (Indonesian Journal of STEM Education, 2021)
This research The purpose of this study was to determine and describe the level of mathematical literacy in  students grade 8th of Junior High School for problem solving of HOTS. The research method that used in this study is descriptive research. The sample in this research were students grade 8th of SMP Negeri 4 Brang Rea. The sampling technique used is purposive sampling with 43 students for the sample. The data collection uses a written test technique in the form of a description that has been declared valid and feasible to use. The data that has been checked are then processed, tabulated, grouped and analyzed so that the research results are obtained showed that 67.44% students had not been able to reach level 4, students who were able to reach level 4 were only 25.58% while for level 5 and 6 were each of 4.65% and 2.33% student, the level of mathematics literacy ability forgrade  8thstudents of SMPN 4 Brang Rea on academic year 2020/2021 problem solving of HOTS is very low with persentase 81.40%.